Revitalizing Seaweed Cultivation in Tourism Practices in Oeseli Village, Rote Ndao Regency - Fauziya Bagawat Sari (Riviera Publishing, 2024)
Oeseli Village is one of the areas known as the largest seaweed producer in Southwest Rote Sub-district, Rote Ndao Regency. Tourism development in Rote Ndao has caused seaweed cultivation to be increasingly marginalized, as seen by the decreasing number of farmers and the conversion of agricultural land to the tourism sector. Conducting this research to develop a revitalization strategy for seaweed cultivation in tourism practices in Oeseli Village is essential. The research method used is qualitative, using descriptive qualitative data analysis techniques. The data sources used were primary and secondary data. Observation, in-depth interviews, and documentation conducted data collection techniques. The determination of informants was done using a purposive sampling procedure. The results of this study indicate that strategies that can be done in the process of revitalizing seaweed aquaculture include the composition of seaweed aquaculture stakeholders according to three actors, aspects of inhibiting factors, and supporting factors of seaweed aquaculture to create efforts that can be done to revitalize seaweed aquaculture. Public awareness of seaweed cultivation should be increased, especially among the younger generation, the nation's next generation. The implication of this research is the need for closer integration between the tourism and seaweed farming sectors in Oeseli Village. Increasing public awareness, especially the younger generation, of the importance of seaweed farming as a sustainable economic potential should continue to be pursued through education, training, and community empowerment programs. In addition, collaboration between the government, tourism actors, and seaweed farmers can create a sustainable economy.